Natural elicitors enhanced suberin polyphenolic accumulation in wounded potato tuber tissues - Dogramaci, Munevver; Sarkar, Dipayan; Finger, Fernando L.; Shetty, Kalidas; Fugate, Karen K. (Frontiers in Plant Science, 2024)
Introduction: Unintended wounding or bruising during harvest or postharvest handling leads to significant tuber loss and imposes economic burden to potato industry. Therefore, finding effective strategies to mitigate wound-related tuber losses is very important from industry perspectives. Formation of protective barrier through accumulation of suberin polyphenolics (SPP) is a natural and initial response of potato tuber tissues to wounding.In this study, efficacy of two natural elicitors, such as chitosan oligosaccharide (COS 0.125 g L -1 ) and cranberry pomace residue (Nutri-Cran 0.125 g L -1 ) was investigated using a mechanically wounded tuber tissue model and by histological determination of SPP formation in five agronomically relevant and red-skin potato cultivars (Chieftain, Dakota Rose, Dakota Ruby, Red LaSoda, Red Norland). Furthermore, the potential role of stress protective metabolic regulation involving phenolic metabolites, proline, and antioxidant enzymes in tuber WH processes were also investigated during 0-9 days after wounding.Results and Discussion: Exogenous treatments of both COS and Nutri-Cran resulted into enhanced SPP formation in wounded surface, but the impact was more rapid with Nutri-Cran treatment in select cultivars. Greater contents of total soluble phenolic, ferulic acid, chlorogenic acid, total antioxidant activity, and superoxide dismutase activity were also observed in elicitor treated tuber tissues at different time points after wounding. Nutri-Cran treatment also reduced the activity of succinate dehydrogenase in Red Norland and Dakota Ruby at 3 d, indicating a suppression in respiration rate. Collectively, these results suggest that Nutri-Cran can be potentially utilized as an effective WH treatment to potato tubers for minimizing wound-related losses.